FAMSi: A Synthetic Biology Approach to the Fast Assembly of Multiplex siRNAs for Silencing Gene Expression in Mammalian Cells - Fang He; Na Ni; Zongyue Zeng; Di Wu; Yixiao Feng; Alexander J. Li; Benjamin Luu; Alissa F. Li; Kevin Qin; Eric Wang; Xi Wang; Xiaoxing Wu; et al. (Elsevier, 2020)
RNA interference (RNAi) is mediated by an ∼21-nt double-stranded small interfering RNA (siRNA) and shows great promise in delineating gene functions and in developing therapeutics for human diseases. However, effective gene silencing usually requires the delivery of multiple siRNAs for a given gene, which is often technically challenging and time-consuming. In this study, by exploiting the type IIS restriction endonuclease-based synthetic biology methodology, we developed the fast assembly of multiplex siRNAs (FAMSi) system. In our proof-of-concept experiments, we demonstrated that multiple fragments containing three, four, or five siRNA sites targeting common Smad4 and/or BMPR-specific Smad1, Smad5, and Smad8 required for BMP9 signaling could be assembled efficiently. The constructed multiplex siRNAs effectively knocked down the expression of Smad4 and/or Smad1, Smad5, and Smad8 in mesenchymal stem cells (MSCs), and they inhibited all aspects of BMP9-induced osteogenic differentiation in bone marrow MSCs (BMSCs), including decreased expression of osteogenic regulators/markers, reduced osteogenic marker alkaline phosphatase (ALP) activity, and diminished in vitro matrix mineralization and in vivo ectopic bone formation. Collectively, we demonstrate that the engineered FAMSi system provides a fast-track platform for assembling multiplexed siRNAs in a single vector, and thus it may be a valuable tool to study gene functions or to develop novel siRNA-based therapeutics.